2022
DOI: 10.1002/jhm.12920
|View full text |Cite
|
Sign up to set email alerts
|

Trends in all‐cause mortality and inpatient and outpatient visits for ambulatory care sensitive conditions during the first year of the COVID‐19 pandemic: A population‐based study

Abstract: Background The impact of the COVID‐19 pandemic on the management of ambulatory care sensitive conditions (ACSCs) remains unknown. Objectives To compare observed and expected (projected based on previous years) trends in all‐cause mortality and healthcare use for ACSCs in the first year of the pandemic (March 2020 to March 2021). Design, Setting and Participants We conducted a population‐based study using provincial health administrative data on general adul population (Ontario, Canada). Outcomes and Measures M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…We tried to minimise referral bias by incorporating a comprehensive definition of the non-OSA group; however, we still missed individuals with undiagnosed OSA 50. The aforementioned biases differentially impact financially and socially disadvantaged populations who tend to be under-represented and, at the same time, are at the highest risk from COVID-19-related outcomes 51. This bias is mitigated by social assistance support for PAP and the location of sleep clinics in lower-income areas in Ontario, and the ATE weighting approach used in a sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tried to minimise referral bias by incorporating a comprehensive definition of the non-OSA group; however, we still missed individuals with undiagnosed OSA 50. The aforementioned biases differentially impact financially and socially disadvantaged populations who tend to be under-represented and, at the same time, are at the highest risk from COVID-19-related outcomes 51. This bias is mitigated by social assistance support for PAP and the location of sleep clinics in lower-income areas in Ontario, and the ATE weighting approach used in a sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…50 The aforementioned biases differentially impact financially and socially disadvantaged populations who tend to be under-represented and, at the same time, are at the highest risk from COVID-19-related outcomes. 51 This bias is mitigated by social assistance support for PAP and the location of sleep clinics in lower-income areas in Ontario, and the ATE weighting approach used in a sensitivity analysis. In addition, we calculated the E-value to adjust for unmeasured confounders (online supplemental table E9).…”
Section: Sleepmentioning
confidence: 99%
“…The authors declare no conflict of interest. Suchita S. Sata MD 1,2 S. Ryan Greysen MD, MHS Email: Suchita.shah.sata@duke.edu; Twitter: @SuchitaSata ORCID Suchita S. Sata http://orcid.org/0000-0002-9773-6174…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In this issue of Journal of Hospital Medicine , Kendzerska et al 2 suggest that the period between peaks in the pandemic waves is only an intermission for the privileged when it comes to health care. The investigators conducted a population‐level study in Ontario, Canada, comparing observed versus expected mortality as well as emergency department (ED) and hospital visits for several ACSCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation